mRNA EXPRESSION OF SOME CHEMOKINES AND THEIR RECEPTORS IN NASAL MUCOSA OF HEALTHY PERSONS - A. A. Bibkova; K. A. Sysoyev; A. V. Semenov; N. E. Lyubimova; N. A. Arsentieva; V. I. Trofimov; Areg A. Totolian (Медицинская иммунология, 2014)
Abstract.  Chemokines  are  a  key  factor  that ensures  the  participation  of  different  cell  types  in the  immunological  protection  of  mucosa.  In  our study  we  chose  some  chemokines  that  ensured  the chemotaxis of neutrophils (CXCL8/IL-8), eosinophils (CCL11/eotaxin,  CCL24/eotaxin-2),  monocytes  and T-lymphocytes  (CCL3/MIP-1α,  CCL4/MIP-1β, CCL5/RANTES),  as  well  as  their  receptors  (CCR1, CCR3, CCR5, CXCR1, CXCR2). mRNA expression of  chemokines  and  their  receptors  in  nasopharyngeal mucosa brush-biopsy specimens determined by RT-PCR in healthy persons, the level of the same chemokines in serum determined by multiplex chemiluminescent assay were analyzed according to smoking. The level of mRNA expression of IL-8 (p < 0.001) and RANTES (p < 0.001) in nasopharynx brush-biopsy specimens and  serum  levels  of  IL-8  (p  <  0.0001)  of  smokers  were  significantly  lower  as  compared  with  nonsmokers. Correlation analysis showed the dependence of the chemokine synthesis on the factor of smoking: the index of smoking (pack/years) is negatively correlated with mRNA levels of IL-8 (r = -0,67 p = 0,003) and RANTES (r = -0,58, p = 0,015) in nasopharynx brush-biopsy specimens and serum concentration of IL-8 (r = -0,89, p = 0,0000002). Thus, these data offer that smokers manifested a defect of the local synthesis of RANTES and IL-8 in nasopharyngeal mucosa in combination with systemic defect of IL-8 production in peripheral blood, that can lead to chronization of bacterial infection and prolonged persistence of viral infection. (Med. Immunol., 2011, vol. 13, N 6, pp 617-622)